Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's solve this problem step by step.
We have the quadratic polynomial [tex]\( p(x) = 5x^2 - 26x + 2m - 9 \)[/tex].
Given that the roots of the polynomial are reciprocal of each other, let's denote the roots by [tex]\( r \)[/tex] and [tex]\( \frac{1}{r} \)[/tex].
### Step 1: Understand the relationship between the roots
For a quadratic polynomial [tex]\( ax^2 + bx + c = 0 \)[/tex], the sum of the roots [tex]\( r_1 \)[/tex] and [tex]\( r_2 \)[/tex] is given by:
[tex]\[ r_1 + r_2 = -\frac{b}{a} \][/tex]
And the product of the roots [tex]\( r_1 \cdot r_2 \)[/tex] is:
[tex]\[ r_1 \cdot r_2 = \frac{c}{a} \][/tex]
### Step 2: Write down the given quadratic polynomial
Here, [tex]\( p(x) = 5x^2 - 26x + 2m - 9 \)[/tex], so we identify:
- [tex]\( a = 5 \)[/tex]
- [tex]\( b = -26 \)[/tex]
- [tex]\( c = 2m - 9 \)[/tex]
### Step 3: Find the product of the roots
Since the roots are reciprocals, the product of the roots [tex]\( r \cdot \frac{1}{r} \)[/tex] is 1.
Using the product of roots formula for quadratic equations:
[tex]\[ r_1 \cdot r_2 = \frac{c}{a} \][/tex]
Substitute [tex]\( c \)[/tex] and [tex]\( a \)[/tex]:
[tex]\[ r \cdot \frac{1}{r} = \frac{2m - 9}{5} \][/tex]
Since [tex]\( r \cdot \frac{1}{r} = 1 \)[/tex]:
[tex]\[ 1 = \frac{2m - 9}{5} \][/tex]
### Step 4: Solve for [tex]\( m \)[/tex]
To find [tex]\( m \)[/tex], we will solve the equation:
[tex]\[ 1 = \frac{2m - 9}{5} \][/tex]
Multiply both sides by 5:
[tex]\[ 5 = 2m - 9 \][/tex]
Add 9 to both sides:
[tex]\[ 5 + 9 = 2m \][/tex]
[tex]\[ 14 = 2m \][/tex]
Divide both sides by 2:
[tex]\[ m = 7 \][/tex]
So, the value of [tex]\( m \)[/tex] is [tex]\( \boxed{7} \)[/tex].
We have the quadratic polynomial [tex]\( p(x) = 5x^2 - 26x + 2m - 9 \)[/tex].
Given that the roots of the polynomial are reciprocal of each other, let's denote the roots by [tex]\( r \)[/tex] and [tex]\( \frac{1}{r} \)[/tex].
### Step 1: Understand the relationship between the roots
For a quadratic polynomial [tex]\( ax^2 + bx + c = 0 \)[/tex], the sum of the roots [tex]\( r_1 \)[/tex] and [tex]\( r_2 \)[/tex] is given by:
[tex]\[ r_1 + r_2 = -\frac{b}{a} \][/tex]
And the product of the roots [tex]\( r_1 \cdot r_2 \)[/tex] is:
[tex]\[ r_1 \cdot r_2 = \frac{c}{a} \][/tex]
### Step 2: Write down the given quadratic polynomial
Here, [tex]\( p(x) = 5x^2 - 26x + 2m - 9 \)[/tex], so we identify:
- [tex]\( a = 5 \)[/tex]
- [tex]\( b = -26 \)[/tex]
- [tex]\( c = 2m - 9 \)[/tex]
### Step 3: Find the product of the roots
Since the roots are reciprocals, the product of the roots [tex]\( r \cdot \frac{1}{r} \)[/tex] is 1.
Using the product of roots formula for quadratic equations:
[tex]\[ r_1 \cdot r_2 = \frac{c}{a} \][/tex]
Substitute [tex]\( c \)[/tex] and [tex]\( a \)[/tex]:
[tex]\[ r \cdot \frac{1}{r} = \frac{2m - 9}{5} \][/tex]
Since [tex]\( r \cdot \frac{1}{r} = 1 \)[/tex]:
[tex]\[ 1 = \frac{2m - 9}{5} \][/tex]
### Step 4: Solve for [tex]\( m \)[/tex]
To find [tex]\( m \)[/tex], we will solve the equation:
[tex]\[ 1 = \frac{2m - 9}{5} \][/tex]
Multiply both sides by 5:
[tex]\[ 5 = 2m - 9 \][/tex]
Add 9 to both sides:
[tex]\[ 5 + 9 = 2m \][/tex]
[tex]\[ 14 = 2m \][/tex]
Divide both sides by 2:
[tex]\[ m = 7 \][/tex]
So, the value of [tex]\( m \)[/tex] is [tex]\( \boxed{7} \)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.